ANALISIS KINERJA RUAS JALAN DR. SUTOMO KOTA BLITAR - Galih Damar Pandulu; M. Sa'dillah; Rifky Aldila Primasworo (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2022)
This study aims to determine the characteristics of the DR. Sutomo and to recognize the performance of the roads. This study utilizes descriptive methods and Guidelines for Indonesian Road Capacity (PKJI, 2014). The results revealed that the value of the Degree of Saturation (DJ) was 0.231 on weekdays in the morning peak hours with service level category B. Meanwhile, during peak hours in the afternoon and evening each had a Degree of Saturation (DJ) value, namely 0.150 and 0.111 with service level category A. The value of the Degree of Saturation (DJ) on weekends in the morning, afternoon and evening peak categories are 0.068, 0.054 and 0.064, respectively, with level of service category A.